Stan poinformowania polskiego społeczeństwa oraz rola politycznego zaangażowania w świetle akcesji Polski do Unii Europejskiej - SMOLIŃSKA, KATARZYNA; JANCZ, JOANNA; PRZEMIENIECKA, AGATA; KUPRIANIEC, KATARZYNA (Rocznik Integracji Europejskiej, 2012)
The prospect of Poland’s joining the EU stirred various emotions and triggered a series of purposeful activities carried out in many dimensions and in numerous areas. Both those at the national and local level were supposed to prepare Poles well for this move. Another desirable outcome concerned the increased political commitment and awareness of Polish society. Even though, in the initial period of negotiations, Poles clearly mistrusted the government and the activity of individual persons, a clear majority were in favor of accession to the EU in the final vote. The political activity and commitment of Polish society advantageously impacted on the level of political culture at that time. The downside involved a profound and distinct division into the supporters and opponents of the accession, both in the media and among political parties.